Fostering reading literacy in transnational education: Practices and challenges at Indonesian overseas schools in the Philippines - Navisatul Izzah; Yunia Tiara Riski; Yuni Suprapto (EduStream: Jurnal Pendidikan Dasar, 2025)
This study aims to examine the implementation of reading literacy practices at Indonesian Overseas Schools (SILN) in the Philippines to understand strategies, outcomes, and challenges in a transnational context. The study is grounded in behaviorist, constructivist, and 21st-century literacy theories to frame the adaptation of national literacy policies in multicultural settings. An exploratory qualitative approach was used, involving semi-structured interviews with four teachers and two students and analyzed through Miles and Huberman’s model and NVivo thematic coding. Findings reveal that structured programs such as DEAR, reading journals, and creative literacy products effectively foster reading habits, despite challenges like limited Indonesian proficiency, resources, and home support. NVivo analysis identified key themes including daily reading routines, personalized teaching strategies, digital integration, and student engagement. Results suggest the need for inclusive, data-driven literacy policies, resource diversification, and teacher training tailored for transnational Indonesian education contexts. This study contributes novel insights into literacy policy adaptation in diaspora schools, emphasizing cultural diplomacy and contextualized literacy strategies abroad.